Intramuscular hematoma due to subcutenous enoxaparin - Altay, Servet; Nurkalem, Zekeriya; Güvenç, Tolga Sinan; Karaca, Mehmet; Özpamuk, Fatma; Çakmak, Hüseyin Altuğ; Karadağ, Nalan (Cerrahpaşa Medical Journal, 2013)
Low molecular weight heparins (LMWH) are generally used for acute coronary syndrome treatment. Rarely, bleeding associated with LMWH’s may lead to severe hemodynamic consequences. Also, intramuscular hematoma may be seen after an accidental injection of enoxaparine intramuscularly (rectus abdominis strain). The disruption of epigastric vessels due to their rich anastomoses nearby the most common injection sites, and pronounced effect of anticoagulation in the elderly and in patients with increased bleeding tendency is suggested as a mechanisms of this rare incident. We report a case with a widespread intramuscular hematoma that had developed after injection of subcutaneous enoxaparine to the abdominal region for the management of acute coronary syndrome.